Martin Luther: Rebel in an Age of Upheaval. Heinz Schilling - Roman SOLOVIY (Богословські роздуми: Східноєвропейський журнал богословʼя)
Book review: Martin Luther: Rebel in an Age of Upheaval. Heinz Schilling, trans. from German (Series “Church History”). Moscow: Izdatel’stvo BBI, 2017. xvi + 710 pp.; ISBN 978-5-89647-358-9